2009
DOI: 10.1016/j.socscimed.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Motivation, money and respect: A mixed-method study of Tanzanian non-physician clinicians

Abstract: Poor quality of care is a major concern in low-income countries, and is in part attributed to low motivation of healthcare workers. Non-physician clinicians (mid-level cadre healthworkers) are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
161
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(170 citation statements)
references
References 31 publications
7
161
0
2
Order By: Relevance
“…13 Healthcare personnel may be poorly supervised, unsupported and not acknowledged, and many work where leadership is weak or even absent. [77][78][79] Even though this cadre has been in existence in Africa for over 30 years, there is still no recognised career path for MLWs, and their level of expertise and qualifi cation is not routinely linked to pay levels. 42 These factors affect the motivation of health workers, which is linked to the quality of care they provide.…”
Section: Impact On Population Healthmentioning
confidence: 99%
“…13 Healthcare personnel may be poorly supervised, unsupported and not acknowledged, and many work where leadership is weak or even absent. [77][78][79] Even though this cadre has been in existence in Africa for over 30 years, there is still no recognised career path for MLWs, and their level of expertise and qualifi cation is not routinely linked to pay levels. 42 These factors affect the motivation of health workers, which is linked to the quality of care they provide.…”
Section: Impact On Population Healthmentioning
confidence: 99%
“…In a mixed-methods study involving interviews, observation, and a survey, Chandler et al (2009) also recognized a range of noneconomic variables playing important roles in the determination of motivational levels among nonphysician clinicians in two regions of Tanzania, but found that salary considered adequate, and commensurate with social status expectations, was a clear prerequisite for motivation, suggesting in contrast that a labor market framework may be of some use.…”
Section: Health Worker Motivationmentioning
confidence: 99%
“…Nedostatak kadra u zdravstvu, a posebno medicinskih sestara je simptom neadekvatne politike zapošljavanja i direktno je srazmjeran ekonomskim prilikama u cijelom svijetu (7). Kada su ljudi na poslu zadovoljni svojim statusom i kad jasno razumiju svoju ulogu i uloge drugih ljudi, raste moral zaposlenih (8,9). Medicinske sestre su nezamjenljiva karika u zdravstvenoj zaštiti, spoj iskustva, znanja i organizaci-onih sposobnosti iako je nažalost, predan i savjestan rad medicinskih sestara u našem društvu marginalizovan.…”
unclassified